Theoretical Study on Horizontal-Type SAW Device with Dual Function of Sensing and Removal of Non-specific Binding - Chen, C.; Wang, Y.; Ao, T.; Hui, G. (Acta Physica Polonica A, 2024)
In this paper, a horizontal-type surface acoustic wave device based on electrode width control interdigital transducer/polymethylmethacrylate/54° Y–X LiNbO3 is proposed to achieve the removal of non-specific binding particles by Rayleigh waves and the detection of meningococcus by Love waves. It is proved that the surface acoustic wave force plays a leading role in the removal of non-specific binding, and the frequency of the acoustic wave also affects the removal effect. The advantage of electrode width control interdigital transducer lies not only in overcoming the shortcomings of bidirectional and focused interdigital transducers, but also in improving the utilization of acoustic waves and the sensitivity of the sensor. When non-specific binding particles are removed by Rayleigh waves, the Love wave sensor shows a sensitivity of 330 Hz/(ng/µL) and a detection limit of 50 pg/µL for meningococcus.